Starch films for agronomic applications: comparative study of urea and glycerol as plasticizers - Versino, Florencia (2018)
This work aims to study the effects of urea, glycerol and their mixture as plasticizers for cassava starch films, regarding their impact on the material structure, water susceptibility, barrier and mechanical properties. All plasticizers were compatible with starchbased matrices, without detecting migration at the plasticizers level tested. In general water related properties were not affected. Plasticizer-polymer interactions as well as those involving water molecules were evidenced by ATR-FTIR spectra. Urea resulted the most efficient plasticizer, since it lowers glass transition temperature values and enhances mechanical properties. The co-plasticization of the starch films with glycerol and urea mixture resulted in poorer mechanical performance, though with higher light absorption which is relevant considering the potential film applications as mulching functionalized cover material.